2021
DOI: 10.3390/jpm11080698
|View full text |Cite
|
Sign up to set email alerts
|

The Gaze Fixation Assessed by Microperimetry: A Useful Tool for the Monitoring of the Cognitive Function in Patients with Type 2 Diabetes

Abstract: Current guidelines recommend annual screening for cognitive impairment in patients > 65 years with type 2 diabetes (T2D). The most used tool is the mini-mental state evaluation (MMSE). Retinal microperimetry is useful for detecting cognitive impairment in these patients, but there is no information regarding its usefulness as a monitoring tool. We aimed to explore the role of retinal microperimetry in the annual follow-up of the cognitive function of patients with T2D older than 65 years. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Some studies have found that fixation stability is related to the cognitive function of patients. 15,16 Fixation stability contributes to the complex network of white matter, superior colliculus, parietal, and frontal cortex, while macular sensitivity depends on the conduction of various links in the visual pathway. 17 Zhu et al 18 have found a significant correlation between mean sensitivity and HbA1c in patients with DR, and time in range (the percentage of time that the target glucose is in the range of 3.9-10.0 mmol/L over 24 hours, as one of the markers of continuous blood glucose testing) of glucose was significant positively correlated with mean sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that fixation stability is related to the cognitive function of patients. 15,16 Fixation stability contributes to the complex network of white matter, superior colliculus, parietal, and frontal cortex, while macular sensitivity depends on the conduction of various links in the visual pathway. 17 Zhu et al 18 have found a significant correlation between mean sensitivity and HbA1c in patients with DR, and time in range (the percentage of time that the target glucose is in the range of 3.9-10.0 mmol/L over 24 hours, as one of the markers of continuous blood glucose testing) of glucose was significant positively correlated with mean sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The device automatically calculates the reliability index, which assesses the accuracy of the test. Furthermore, according to our previous results [ 10 , 13 ] we evaluated as part of GF: the bivariate contour ellipse area, as the preferred retinal loci to calculate fixation stability (BCEA): BCEA63% (1 standard deviation) and BCEA95% (2 standard deviations) areas. The BCEA is measured as a bivariate contour ellipse, expressed in “º 2 ”.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, by adding the GF parameters to the RS the probability to identify cognitive impairment significantly increased in an independent manner, with a sensitivity of 72.7% and sensibility of 87.9% [ 12 ], converting the retinal microperimetry into a potential useful tool for the screening of MCI in patients with T2D > 65 years. Additionally, we have recently evaluated the usefulness of retinal microperimetry as a monitoring tool for the cognitive function in patients > 65 years with T2D [ 13 ]. The annual worsening in cognitive function went in parallel with worsening of GF, suggesting this parameter can be a reliable and subtler tool for the monitoring of the cognitive function in patients with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have recently evaluated the usefulness of retinal microperimetry as a monitoring tool for the cognitive function in patients >65 years with T2D ( 36 ). We found that the worsening in cognitive function went in parallel with worsening of gaze fixation, suggesting this parameter can be a reliable and more subtle tool for the monitoring of the cognitive function in patients with type 2 diabetes.…”
Section: New Emerging Methods For Screening and Monitoring Of Cogniti...mentioning
confidence: 99%